2021
DOI: 10.1186/s12939-021-01463-w
|View full text |Cite
|
Sign up to set email alerts
|

Are Nepal’s water, sanitation and hygiene and menstrual hygiene policies and supporting documents inclusive of disability? A policy analysis

Abstract: Purpose This study assesses the inclusion of disability in Nepal’s policy and guidance relevant to water, sanitation and hygiene (WASH), and menstrual hygiene management (MHM) in comparison to gender. We investigated both policy formulation and implementation, using the Kavrepalanchok district as a case study. Materials and methods We used the EquiFrame framework, adapted for disability and gender, and focusing on WASH and MHM. Ten Nepali policies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…A consistent finding across studies which explore inclusive WASH is that caregivers are not recognized for the critical support roles they often play in supporting people with disabilities and older adults with WASH and maintaining personal hygiene (21,26,30,(49)(50)(51). Our study found a greater emphasis on caregivers (Family resource) than in other studies (37,39,48). As noted above, though this indicates an awareness of caregivers' importance, this attention did not translate into clearly articulated actions for this group, meaning they were also unlikely to benefit extensively from these efforts.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A consistent finding across studies which explore inclusive WASH is that caregivers are not recognized for the critical support roles they often play in supporting people with disabilities and older adults with WASH and maintaining personal hygiene (21,26,30,(49)(50)(51). Our study found a greater emphasis on caregivers (Family resource) than in other studies (37,39,48). As noted above, though this indicates an awareness of caregivers' importance, this attention did not translate into clearly articulated actions for this group, meaning they were also unlikely to benefit extensively from these efforts.…”
Section: Discussionsupporting
confidence: 81%
“…However, the total number of references made to individual core concepts was limited, particularly about aging, which was woefully low. Across this and other similar studies, Individualized services and Access are referenced consistently highly, whilst Participation, Capability based services, and Accountability receive little attention (37,39,48). Some may think this unsurprising because many governments, organizations, and institutions aim to increase access to WASH services, particularly in an emergency setting.…”
Section: Discussionmentioning
confidence: 71%
“…A growing body of data reveals that people with disabilities face additional challenges in realising their menstrual health in LMICs. This issue is particularly evident for people with intellectual disabilities who often rely on caregivers [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. For instance, a recent study in Vanuatu highlighted that women and girls must independently collect their own water, bathe, and wash their reusable menstrual materials when menstruating.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, women and girls with intellectual disabilities are particularly disadvantaged when menstruating [ 6 ]. Evidence from different settings demonstrates that management strategies applied by caregivers include isolating and physically restraining people with intellectual disabilities during menstruation and, in some cases, sterilisation to cease menstruation [ 5 , 6 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…33 , 34 Focusing on schools was one of its dimensions, but it remained a barrier 17 in addressing gender equality and inclusive accessibility. 23 , 35 As a result, water, sanitation, and hygiene (WASH) in schools refer to a mix of technical and human development elements that are required to create a healthy school environment and establish proper health and hygiene behaviors. 36 Safe water supply, sanitation facilities, excellent hygiene practice, menstrual hygiene management, and solid and liquid waste management are among the minimal standards for school WASH programs.…”
Section: Introductionmentioning
confidence: 99%